LEVEL OF CONSCIOUSNESS STUDIES STUDENT COMPARATIVE MEN WITH WOMEN OF IMPLEMENTATION SCHOOL DISCIPLINE IN CLASS VII MTs DARUL Huffazh - Annisa Mei Pratiwi; Adelina Hasyim; Yunisca Nurmalisa (FKIP Unila, 2012)
The purpose of this study is to describe and examine the differences in the level of awareness among the male students to female students on the implementation of school discipline in Class VII MTs Daarul Huffazh Pesawaran Academic Year 2012/2013. This study uses descriptive. Samples numbered 38 people. Methods This study used a descriptive method with a sample of 38 respondents. Principal techniques of collection using a questionnaire. Analysis using the percentage formula. To test for differences in the level of awareness of male students to female students on the implementation of the school rules then used the Mann-Whitney U-Test. The results are as follows: (1) The level of awareness of male students and female students on the implementation of school discipline included in the category are quite aware. (2 There are different levels of awareness of male students and female students on the implementation of school discipline. Keywords: Level of Consciousness, Discipline, Masculinity, Femininity